Idiopathic eruptive macular pigmentation: Report on two cases - Grover Sanjiv; Basu Atoshi (Wolters Kluwer Medknow Publications, 2010)
Idiopathic eruptive macular pigmentation (IEMP) is a rather under-reported condition of unknown etiology. Clinically consisting of benign hyperpigmented macules, the condition is characterized histopathologically by dermal melanization. It must be differentiated from lichen planus pigmentosus, erythema dyschromicum perstans, fixed drug eruption and mastocytosis.